2013
DOI: 10.2147/rmhp.s40553
|View full text |Cite
|
Sign up to set email alerts
|

Fever without source in infants and young children: dilemma in diagnosis and management

Abstract: BackgroundThere is controversy surrounding the management of young children who have a fever without a source (FWS). Several strategies have been designed with the purpose of managing children with FWS.AimsTo assess the applicability of a standardized guideline for children up to 36 months of age with FWS.SettingPediatric emergency unit, Al-Adan Hospital, Kuwait City, Kuwait, from May 2011 to October 2011.DesignProspective, cross-sectional study.Methods and materialsThe study involved children with FWS up to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…It is important to note that the majority of the sepsis studies were conducted at intensive care units, where patients with severe sepsis and septic shock, and late stages of sepsis continuum, were included. Our finding highlights an important difference between these two populations, because in EDs, the vast majority of children present with benign and self-limited viral infections [25]. In addition, in our study, most of the patients were younger than 1 year of age.…”
Section: Discussionmentioning
confidence: 55%
“…It is important to note that the majority of the sepsis studies were conducted at intensive care units, where patients with severe sepsis and septic shock, and late stages of sepsis continuum, were included. Our finding highlights an important difference between these two populations, because in EDs, the vast majority of children present with benign and self-limited viral infections [25]. In addition, in our study, most of the patients were younger than 1 year of age.…”
Section: Discussionmentioning
confidence: 55%
“…Вероятно, это связано с широким индиви-дуальным разнообразием симптомов, и прежде всего с субъективностью их оценки [17,18]. Важное место в диагностике ТБИ у детей с лихорадкой занимают лабо-раторные исследования [19]. Наиболее информативными и надежными считают показатели гемограммы (общее число лейкоцитов, нейтрофилов), а также некоторые сывороточные параметры, в частности прокальцитонин (ПКТ) и С-реактивный белок (СРБ) [20].…”
Section: вопросы современной педиатрииunclassified
“…Multivariate logistic regression analysis of independent markers to be used in determining SBI Lacour et al7 reported a prevalence of SBI of 27% in well-appearing FWS patients aged under 3 months and Elhassanien et al10 reported a prevalence of 6.8% in children under the age of 3 years. Well-appearing children with FWS aged between 3 months and 17 years were enrolled in our study, and the prevalence of SBI was 11.9%.While some studies have reported an association between body temperature elevation and development of SBI,…”
mentioning
confidence: 99%